Qualitative analysis of front-of package labeling policy interactions between stakeholders and Health Canada - Jawad, Aalaa; Mulligan, Christine; Savona, Natalie; L'Abbé, Mary R. (Frontiers in Public Health, 2023)
Background Front-of-package labelling regulations proposed by Health Canada in their Healthy Eating Strategy (2016) were finally passed in 2022, but remain unimplemented. This study analysed interactions that occurred between stakeholders and government related to this policy proposal to identify key themes and policy implications. Methods A qualitative framework analysis was conducted on publicly available documents for stakeholder correspondences related to front-of-package that occurred between 2016-2019 in Health Canada’s Meetings and Correspondence on Healthy Eating database. Five sequential steps were applied: familiarisation, identifying a thematic framework, indexing, charting, and mapping and interpretation. A complex systems (i.e. a dynamic system with multiple interconnecting components) lens was incorporated in the final step to deepen the analysis. Results 173 documents were included, the majority from industry stakeholders (n=108, 62.4%). Three overarching themes were identified: industry trying to control the agenda and resist regulation; questioning the evidence supporting the policy and its impact on the agri-food industry; and dismissing the need and effectiveness of the policy. Incorporating a complex system lens found industry and non-industry stakeholders held markedly different perspectives on how cohesive the system defined by the front-of-package labelling policy was, and the policy impact on its stability. Economic and opportunity costs were the main trade-offs, and symbol misinterpretation considered an unintended consequence by industry. Finally, some stakeholders argued for wider policy scope incorporating more products, while others requested a narrower approach through exemptions. Conclusions Interactions with industry stakeholders on health food policy proposals require careful consideration, given it may suit their interests to generate delays and policy discordance. Explicitly setting out the principles of engagement and actively encouraging non-industry stakeholder representation provides a more balanced approach to policy consultation and development.